Impact of Social Media on Contemporary Indonesian Language Usage - Anita Candra Dewi; Nurul Fatma; Nurazizah Nurazizah; Rivika Leban; Wahyudi Wahyudi; Adzgal. S (International Journal of Global Sustainable Research, 2023)
Language is a very crucial sense of communication in culture and society. Indonesian as the official state language has a special role in maintaining Indonesian national and cultural identity. This research is qualitative research using descriptive analysis techniques with library research where this research attempts to describe existing phenomena, which are taking place currently or in the past. This research shows that social media has a significant impact on contemporary Indonesian language use. As a result, efforts need to be made to increase ethical awareness and the quality of the Indonesian language on these platforms. One step that can be taken is to provide education regarding the ethics and quality of using Indonesian on social media. Apart from that, there needs to be strict sanctions from law enforcement officials against social media users who violate the ethics and quality of the Indonesian language.